Adherence to statin therapy in patients with high and very high cardiovascular risk in real clinical practice - V. I. Podzolkov; A. E. Bragina; L. V. Vasil’eva; Yu. P. Grintsevich; Yu. N. Rodionova (Сеченовский вестник)
Despite the proven efficacy of lipid-lowering therapy, adherence to long-term statin therapy in patients with cardiovascular disease remains low.Aim. To study adherence to long-term statin therapy and factors associated with adherence in patients with high and very high cardiovascular risk (CVR) in real clinical practice.Materials and methods. The single-center cohort study included 53 patients (mean age 68.1 ± 10.2 years) with high or very high CVR on the SCORE scale and have been taking statins for at least 3 months prior to inclusion in the study. The level of low-density lipoprotein cholesterol (LDL-C), cognitive impairment (MoCA test), anxiety and depression (HADS scale), presence of senile asthenia (FRAIL scale), M. Charlson comorbidity index were assessed. Adherence to statin therapy was assessed using the original questionnaire. The correlation between patient adherence and ordinal variables for the scores of the studied scales was studied.Results. Completely adherent to statin therapy were only 12 (22%) patients, 14 (26%) were insufficiently adherent, 27 (51%) were non-adherent. The target level of LDL-С was achieved in 13 (25%) patients. 38 (72%) patients showed a decrease in cognitive functions; a positive correlation was found between adherence and the MoCA test (r = 0.44, p = 0.04). Clinical and subclinical depression and anxiety were noted in 12 (23%) and 14 (26%) patients, respectively. A statistically significant negative correlation was found between adherence and depression (r = –0.32; p = 0.04) and a positive correlation between adherence and anxiety (r = 0.44; p = 0.04). There was no statistically significant correlation between adherence and the FRAIL fragility scale, as well as the M. Charlson comorbidity index.Conclusions. Depression and cognitive decline are associated with decreased adherence to statin therapy.